IMPROVING STUDENTS’ READING COMPREHENSION THROUGH DIRECTED READING THINKING ACTIVITY (DRTA) METHOD - Azahro, Nadiera Yulia; Hamid, Radiah; Hamid, Sitti Maryam (English Language Teaching Methodology, 2024)
The objective of the research is to find out whether Directed Reading Thinking Activity (DRTA) Strategy able to improve the students’ reading comprehension at the Twelfth Grade Students of SMA Negeri 3 Bulukumba. The method of the research used pre-experimental design. It consisted of pre-test, treatment and post-test design. The population of this research is the twelfth grade students of SMAN 3 Bulukumba. The researcher used Purposive Sampling Technique which involve one class XII IIS 3. Total sample are 29 students. The result of the study showed that Directed Reading Thinking Activity (DRTA) Method could improve the students’ reading comprehension especially in literal reading comprehension at the Twelfth Grade Students of the SMAN 3 Bulukumba. It was proved that the mean score of Pre-Test is 64 and the Post-Test mean score is 70,6. Based on the difference from the mean score students get in reading comprehension show the improvement from pre-test to post-test where the increase of students reading comprehension increased by 12%. The improvement of students’ achievement significantly. Thus, the null hypothesis (H0) is discarded, while the alternative hypothesis (H1) is accepted. The researcher emphasizes that the Directed Reading Thinking Activity (DRTA) made active because its activity foresees various strategy and it was meaningful for the daily students life. Also, Directed Reading Thinking Activity (DRTA) strategy in the learning reading comprehension is very effective, because the students more easy to understand with the prediction that identifying main idea and supporting details and it can be seen from the result of students’ reading scores is better.